Into the Wild: Working with Preverbal Experiences in a Group. Issue 1 (2nd January 2018) - Price, Jordan
ABSTRACT: This article begins with a metaphor of being in the wilderness at night to demonstrate the group analyst's reliance on implicit experiences. The entrenched patterns of group members are rooted in a developmental phase before words and symbolization are available to manage distress. These group members enact in the here-and-now a relational dysfunction fixed in early attachment patterns. The defenses they induce resist interpretation and traditional analysis. The group analyst must be willing to sink into these non-verbal affective states expressed unconsciously yet communicated and to work with the member on an emotional, non-interpretative level. A brief review of affect regulation theory, attachment theory, and infant studies supports this treatment approach. Two vignettes follow to illustrate the nature of working in this visceral and intuitive manner while maintaining an observing ego.